Heat transfer and frictional pressure drop of crop fiber suspensions in closed conduit flow and nanofluid flow in backward-facing step / Syed Muzamil Ahmed - Syed Muzamil, Ahmed (2017)
Study of heat transfer and frictional pressure losses in fiber suspension a non- Newtonian fluid flow is one of the significant scientific interests as the characteristics of fiber suspension flow considerably changes with the addition of little amounts of fiber. The characteristics of the fiber suspension flow depends on the shear stress, consistency, fiber source, fiber properties, the treatments done on the fibers and the fluid velocity. The non-Brownian motion of fibers in suspension flow are found in many applications, such as fiber composites, pulp and paper, textile, long-chain polymer etc. There are noticeable investigations conducted on properties of fiber suspensions but they are mainly wood pulp and family of pine groups. Study of the hydrodynamic behavior of non-wood fiber suspensions has become imminent due to increasing demand for non-wood fibrous materials. The nescience of non-wood fiber suspensions flowing in pipe elevated concerns regarding handling of non-wood fiber suspensions in papermaking process. As there are no significant reporting regarding non-wood pulp fibers flowing in pipes. So, it has become essential to investigate heat transfer and pressure drop of non-wood fiber suspensions in pipeline flow. A set up was built with a straight pipe test section to evaluate the heat transfer and frictional pressure drop characteristics of turbulent flowing pulp fiber suspensions, where the data were taken at different velocities and consistencies at constant heat flux. Several experiments were conducted for different types of non- wood pulp fibers (Kenaf core, Kenaf bast, blend of non-wood and blend of wood pulp fibers) at different consistencies and flow rates. The measured heat transfer coefficient (hc) and frictional pressure drop (ΔP/L) data were correlated with the fiber and paper properties.The results revealed that most of the fiber and paper properties could be correlated with both hc and ΔP/L data. A specific range of hc or ΔP/L can be used to monitor quality variations of fibers in suspension long before the paper is made, so that corrective action can be taken and the amount of rejected paper production could be minimized. The magnitude of hc and ΔP/L were found depending on flow velocity, consistency, fiber population, fiber length, flexibility, and fiber surface topography. Nanofluid flow and heat transfer to fully developed turbulent forced convection flow in a uniformly heated tubular horizontal backward-facing step were studied experimentally. Five different types of water based (Al2O3, SiO2 and MWNT) nanofluids have experimentally investigated. The experiments were conducted for concentration range of 0 to 0.1 wt.% and Reynolds number of 4000 to 16000 at uniform and constant heat flux. Heat transfer coefficient increases nonlinearly with the increase of both the concentration and Reynolds number. The peak of the heat transfer coefficient has occurred after the sudden expansion and it moved far from the step height with the increase of Reynolds number for both the cases of pure water and nanofluids. The pressure drop variation increases with the increase of Reynolds number and nanoparticles concentration but the changes observed are insignificant in the present range of investigation.